2014
DOI: 10.1186/1471-2458-14-655
|View full text |Cite
|
Sign up to set email alerts
|

Associations between objectively assessed child and parental physical activity: a cross-sectional study of families with 5–6 year old children

Abstract: BackgroundA number of studies have suggested that there is a need to increase the physical activity levels of children. Parents are important influences on children’s behaviour. There is a lack of information about whether there are associations between the physical activity levels of young children and their parents. The current study examined the associations between the physical activity (PA) of parents and their children at age five to six years old, and determined whether any associations differed by chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
70
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 30 publications
6
70
1
Order By: Relevance
“…Our results of the positive association between a mother's MVPA and a child's MVPA are in line with the recent study with 5-year-old children (Jago et al, 2014), in which it was found that every 10 minutes increase in parent's MVPA was associated with 1 minutes increase in MVPA of a child. The association in the current study was weak, but significant.…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…Our results of the positive association between a mother's MVPA and a child's MVPA are in line with the recent study with 5-year-old children (Jago et al, 2014), in which it was found that every 10 minutes increase in parent's MVPA was associated with 1 minutes increase in MVPA of a child. The association in the current study was weak, but significant.…”
Section: Discussionsupporting
confidence: 95%
“…Our results show slightly lower percentages than the results from a study (Jago et al, 2014) where 70% of boys and just over 50% of girls of a similar age and with the same cut points for PA intensity levels as in our study, exceeded the recommendation of over 60 minutes of MVPA. Other studies also exist on this matter, but the different age ranges and the reporting decisions (counts per minute or PA levels) makes it hard to accurately compare the results.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…The findings indicated that the explicit modelling and MVPA of fathers were significantly related to the MVPA duration of boys, whereas the explicit modelling of mothers was significantly associated with the MVPA of girls. These findings further support the notion that parental support and MVPA are crucial in shaping MVPA in elementary and middle school-aged children (Craig et al, 2013;Davison, 2004;Davison and Jago, 2009;Davison et al, 2003;Jago et al, 2010Jago et al, , 2014Raudsepp, 2006). Fathers and mothers who serve as good role models effectively promote boys' and girls' MVPA participation respectively.…”
Section: Discussionsupporting
confidence: 80%